If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -88 = (-8) * y Solving -88 = -8y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '8y' to each side of the equation. -88 + 8y = -8y + 8y Combine like terms: -8y + 8y = 0 -88 + 8y = 0 Add '88' to each side of the equation. -88 + 88 + 8y = 0 + 88 Combine like terms: -88 + 88 = 0 0 + 8y = 0 + 88 8y = 0 + 88 Combine like terms: 0 + 88 = 88 8y = 88 Divide each side by '8'. y = 11 Simplifying y = 11
| 8m=-16+40 | | 41-11=5(x-3) | | 10=x-x-5 | | 2(2y+3)+2=4y+5 | | 1650=8x+2t^2 | | 2(5-2x)=15+6x | | 6x+4=4(3x+2) | | -100x^2+25x-1=0 | | 8m=6+2m | | (x-6)(5x^2+x-8)= | | 3y+3=312 | | 5y+25=-5-y | | -2x+5=x-12 | | 15-2=15 | | (x^3+4x^2-5x)-(4x^3+x^2-7)= | | -x(-8)-4y=16 | | -4x+9=35 | | 13k+3(k+11)=8k+-7 | | 3y+2=12-y | | 6b-.2=7b | | 5d-27=108 | | 25(C-55)=23750 | | X(2x+1)+4(2x+1)=0 | | 2*(3t^2)*(4t^2-1)=x | | 19+x=14 | | 2k+-2.6=12 | | -6t-8=-7t | | f(x)=3x^3-x^2+5x | | -8g=-9g-2 | | 3p-3=2 | | N-6=2n-16 | | X-.3x=114 |